Pengaruh Pelatihan Dan Kompetensi Terhadap Kinerja Anggota Organisasi Dengan Kepuasan Anggota Sebagai Variabel Intervening (Studi Pada UKM Universitas Islam Malang TA. 2023) - Mutmainna, Siti; Pardiman, Pardiman; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the influence of training and competency on mediating performance by member satisfaction in UKM Islamic University of Malang. The type of research used is quantitative research by distributing questionnaires. Sampling in this study used simple random sampling, namely by using simple random sampling to serve as a sample using the Slovin formula with a sample size of 102 respondents. Data processing uses SEM-AMOS. The data analysis method used in this research is by using outer model and inner model testing. Based on the research results, it is known that training and competence have a significant effect on performance, training and competence do not have a significant effect on satisfaction, satisfaction has a significant effect on performance and satisfaction can mediate training and competence on performance. Keywords: Training, Competency, Performance and Satisfaction